Test Methods for Compression Members
DOI: 10.1520/stp43785s
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Buckling of Plates with Residual Stresses

Abstract: This report is a summary of local buckling tests of plate elements in square columns built-up by welding. The experiments were conducted to verify theories for the elastic and elastic-plastic buckling of plates with emphasis on the effect of residual stress. This was part of a general study on the strength of welded columns and the influence of residual stress on plate buckling $ Both ASTM A7 and A5l4 steels were used. The square section simulated plates simply supported at the unloaded edges, and the length o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 0 publications
1
40
0
Order By: Relevance
“…In Figure 9, the results from the tensile coupon tests carried out in the present study on both the flat (F) and corner (C) material have been combined with those collated from the literature, reported in references [11][12][13][27][28][29][30][31][32][33][34][35][36], and used to assess the variation of the f u /f y ratio with yield stress f y . The observed trend of decreasing values of f u /f y with increasing yield stress f y is in line with previous findings [8,10,37], and reflects the fact that strengthening mechanisms used in the production of high strength steels bring about significant increases in the yield strength, but have less influence on the ultimate tensile strength [1].…”
Section: Assessments Of Materials Ductility Requirementsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 9, the results from the tensile coupon tests carried out in the present study on both the flat (F) and corner (C) material have been combined with those collated from the literature, reported in references [11][12][13][27][28][29][30][31][32][33][34][35][36], and used to assess the variation of the f u /f y ratio with yield stress f y . The observed trend of decreasing values of f u /f y with increasing yield stress f y is in line with previous findings [8,10,37], and reflects the fact that strengthening mechanisms used in the production of high strength steels bring about significant increases in the yield strength, but have less influence on the ultimate tensile strength [1].…”
Section: Assessments Of Materials Ductility Requirementsmentioning
confidence: 99%
“…Test data on high strength steel stub columns have been collected and carefully analysed in this section to assess the suitability of the Class 3 [5] limit for internal elements in compression. Figure 13 compares the EN 1993-1-1 Class 3 limit for internal elements in compression (c/tε = 42) with the results of stub column test on high strength steels from this study and those collected from the literature [11][12][13][45][46][47][48][49][50][51][52]. Stub column test data on lower steel grades, with nominal yield strength between 260 N/mm 2 and 450 N/mm 2 , from [13,49,[53][54][55][56] have also been presented in Figure 13 for comparison purposes.…”
Section: Assessment Of Eurocode Class 3 Slenderness Limits For Internmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1967, Nishino, Ueda [3] et al considered the effect of residual stress on local buckling of HSS stub columns. The work is mainly focusing on the magnitudes and distributions of HSS (yield strength 717 MPa, 800 MPa) welded box sections which has a thickness of plates of 6.5 mm and width-thickness ratios of 26.2 and 44.…”
Section: Previous Residual Stress Researches In Hss Box-sectionmentioning
confidence: 99%
“…However, most of this research has focused on the behaviour of bare steel structures, and only a few research findings are related to composite steel and concrete structures. Rasmussen and Hancock [6,7], Usami and Fukumoto [8], Nishino et al [9], McDermott [10] and Shi et al [11] investigated experimentally the buckling behaviour of 690 MPa HS steel columns under compression, Ban et al [12] and Wang et al [13] reported the overall buckling performance of 460 MPa HS steel pin-ended columns and proposed a design method on the basis of a number of parametric studies, while Ban et al [14] and Shi et al [15] investigated the overall and local buckling behaviour of 420 MPa steel angle columns, with design approaches being proposed. It was identified in this work that the buckling behaviour of HS steel columns is improved significantly due to the less-severe effects of residual stress in comparison to conventional mild steel columns.…”
Section: Introductionmentioning
confidence: 99%